Indonesia’s tuna industry: Policies and market barriers - Zainuddin, Sriwiyata Ismail; Ismira, Andi; Mappatunru, A.; Soreang, Ester Lita; Edo, Gabriel (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
This paper aims to explore the multifaceted dynamics of Indonesia’s tuna export sector, focusing on key internal and external factors influencing its growth. Internally, the study examines the policies from the Ministry of Maritime Affairs and Fisheries aimed at reducing Illegal, Unreported, and Unregulated fishing. While these initiatives offer notable ecological benefits, they have also led to economic challenges, particularly in reducing the export potential and revenue from both fresh and processed tuna products. Externally, the paper assesses the significant barriers posed by global trade regulations, including both tariff and non-tariff measures, which impede Indonesia’s ability to fully leverage its tuna export potential. These complex international trade constraints hinder Indonesia's competitiveness, particularly in markets like the EU and the U.S., where stringent non-tariff barriers, such as quality standards and traceability requirements, place additional pressure on the industry. Using a qualitative research approach and comprehensive literature review, this study advocates for a balanced and inclusive approach to fisheries management. This approach should prioritize both ecological sustainability and economic development, aiming to improve Indonesia's processing capabilities and better position it in the global tuna value chain.